EFFECTS OF EXTENDED VALUE CHAIN ACTIVITIES ON PROFIT EFFICIENCY IN MALAYSIAN PLANTATION COMPANIES (Malaysian Management Journal, 2023)
The palm oil industry in Malaysia is the main driver of Malaysia’s agricultural sector due to its significant contribution. High demandand attractive earnings of palm oil have attracted high participation from plantation companies in this industry. Therefore, this studyaimed to assess the level of profit efficiency of plantation companies involved in different value chain activities, as well as the factors that influence the profit efficiency of these plantation companies. A total of 40 Malaysian plantation companies listed in Bursa Malaysia from 2000 to 2018 with different value chain activities were examined using panel data. The evaluation of profit efficiency was based on data analysis, which included working capital costs, labour costs, and property, plant, and equipment (PP&E) costs that affect the plantation companies’ profit function. The parametric approach, also known as Stochastic Frontier Analysis (SFA), was used to assessthe profit efficiency of these plantation companies empirically. The results revealed that the average profit efficiency of 40 plantationcompanies was 60.3 percent, implying that an estimated 39.7 percent of profit was lost due to a combination of technical inefficiencies and allocative inefficiencies in plantation companies. Other findings were based on value chain activity categories (pure upstream plantation companies and downstream integrated plantation companies), whereby downstream integrated plantation companies had the highest profit efficiency (76.6%) when compared to the pure upstream plantation companies (54.2%). As a result, the study showed that plantation companies engaged in extended value chain activities were more profit efficient than plantation companies that did not extend their value chain activities (referring to pure upstream plantation companies).